2014
DOI: 10.1111/papr.12242
|View full text |Cite
|
Sign up to set email alerts
|

The Pain Self‐Efficacy Questionnaire: Cross‐Cultural Adaptation into Italian and Assessment of Its Measurement Properties

Abstract: The Pain Self-Efficacy Questionnaire (PSEQ) is a patient self-reported measurement instrument that evaluates pain self-efficacy beliefs in patients with chronic pain. The measurement properties of the PSEQ have been tested in its original and translated versions, showing satisfactory results for validity and reliability. The aims of this study were 2 fold as follows: (1) to translate the PSEQ into Italian through a process of cross-cultural adaptation, (2) to test the measurement properties of the Italian PSEQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
69
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(79 citation statements)
references
References 39 publications
9
69
1
Order By: Relevance
“…The same studies also highlighted that the role of mediator of pain self‐efficacy was more robust relevant than other frequently assessed psychosocial factors, such as fear of movement . While the role of mediators of these psychosocial constructs has been well investigated, the associations of these constructs to main outcomes (i.e, pain intensity and disability) have only been studied with simple correlations, finding pain self‐efficacy correlating higher than fear of movement . However, the study of simple correlations between constructs does not include the possibility to assess and control for the role of potential confounders .…”
Section: Introductionmentioning
confidence: 99%
“…The same studies also highlighted that the role of mediator of pain self‐efficacy was more robust relevant than other frequently assessed psychosocial factors, such as fear of movement . While the role of mediators of these psychosocial constructs has been well investigated, the associations of these constructs to main outcomes (i.e, pain intensity and disability) have only been studied with simple correlations, finding pain self‐efficacy correlating higher than fear of movement . However, the study of simple correlations between constructs does not include the possibility to assess and control for the role of potential confounders .…”
Section: Introductionmentioning
confidence: 99%
“…The study did not consider the possibility that low self-efficacy in those with high symptom distress was actually caused by the distress itself, which is a plausible explanation. In fact, Chiarotto et al (2014) found that cancer patients on pain medication have higher rates of self-efficacy, which would appear to show that distress reduces self-efficacy, rather than the other way around, as assumed in the above study.…”
mentioning
confidence: 63%
“…Most items usually point out a beliefs level to carry out daily activities/chores higher than the scale's mean point; item 7 points out the individuals' lower beliefs level when dealing with pain without using medicines. In view of a similar result, Di Pietro et al 10 and Chiarotto et al 11 proposed that this item could present a high potential to differentiate the individuals' behaviors when facing pain, as it approaches the self-efficacy belief in dealing with pain using no medicines. Thus, this item could have clinical aggregate value in the assessment of pain-related self-efficacy.…”
Section: Discussionmentioning
confidence: 90%
“…The pain self-efficacy questionnaire (PSEQ) is composed of 10 items arranged in a unifactorial model and was developed to investigate the degree of trust that patients with chronic pain have on themselves to perform daily activities or functions. The use of PSEQ has grown with the increase in translations and adaptations to different languages 3,[5][6][7][8][9][10][11][12] . In spite of its wide use, few studies 5,7,8,11 have shown evidence of the instrument's psychometric properties in different samples based on a confirmatory analysis of the psychometric properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation